M-Cadherin Is a PAX3 Target During Myotome Patterning - Esteves de Lima, Joana; Bou Akar, Reem; Mansour, Myriam; Rocancourt, Didier; Buckingham, Margaret; Relaix, Frédéric (Frontiers in Cell and Developmental Biology, 2021)
PAX3 belongs to the paired-homeobox family of transcription factors and plays a key role as an upstream regulator of muscle progenitor cells during embryonic development. Pax3-mutant embryos display impaired somite development, yet the consequences for myotome growth and patterning have not been characterized. The early myotome is formed by PAX3-expressing myogenic cells that delaminate from the dermomyotomal lips and migrate between the dermomyotome and sclerotome where they terminally differentiate. Here we show that in Pax3-mutant embryos, myotome fibers are misaligned, detached from the edges, and lose the regionalization of the structural protein Desmin. In addition, this phenotype is more severe in embryos combining Pax3-null and Pax3 dominant-negative alleles. We identify the adhesion molecule M-Cadherin as a PAX3 target gene, the expression of which is modulated in the myotome according to Pax3 gain- and loss-of-function alleles analyzed. Taken together, we identify M-Cadherin as a target of PAX3, associated with the patterning of the myotome fibers.